2016
DOI: 10.1371/journal.pone.0168400
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptation to Low Copper in Candida albicans Involving SOD Enzymes and the Alternative Oxidase

Abstract: In eukaryotes, the Cu/Zn superoxide dismutase (SOD1) is a major cytosolic cuproprotein with a small fraction residing in the mitochondrial intermembrane space (IMS) to protect against respiratory superoxide. Curiously, the opportunistic human fungal pathogen Candida albicans is predicted to express two cytosolic SODs including Cu/Zn containing SOD1 and manganese containing SOD3. As part of a copper starvation response, C. albicans represses SOD1 and induces the non-copper alternative SOD3. While both SOD1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 67 publications
4
44
0
Order By: Relevance
“…CrpA mediated transport or AtfA ROI activation) were sufficient to rescue Δ aceA survival blurs the line between which fungal mechanism is most important and – similar to the intertwined contributions of copper transport and PHOX systems in host response above – reinforces the interconnectedness of both fungal responses to copper extremes. Recent studies in C. albicans show a distinct response of ROI defense mechanism towards different copper-environments during infection (Broxton and Culotta, 2016; Li et al, 2015), suggesting that a similar connection as demonstrated in A. fumigatus in this study could represent a common maneuver in other fungal pathogens.…”
Section: Discussionsupporting
confidence: 80%
“…CrpA mediated transport or AtfA ROI activation) were sufficient to rescue Δ aceA survival blurs the line between which fungal mechanism is most important and – similar to the intertwined contributions of copper transport and PHOX systems in host response above – reinforces the interconnectedness of both fungal responses to copper extremes. Recent studies in C. albicans show a distinct response of ROI defense mechanism towards different copper-environments during infection (Broxton and Culotta, 2016; Li et al, 2015), suggesting that a similar connection as demonstrated in A. fumigatus in this study could represent a common maneuver in other fungal pathogens.…”
Section: Discussionsupporting
confidence: 80%
“…1D). As previously mentioned, a major adaptation to low Cu in C. albicans involves Cu sparing whereby the major cuproprotein Sod1 is downregulated (7,9). CP can induce Mnsparing responses in Staphylococcus aureus (50,51), and we tested whether the same is true for Cu sparing in C. albicans.…”
Section: Resultsmentioning
confidence: 92%
“…By repressing SOD1, Cu is spared to maintain activity of Cu-dependent cytochrome c oxidase, essential for mitochondrial respiration. Sod1 is a major cuproenzyme of the cell, and any loss in Sod1 can be significant in terms of Cu sparing (9). Evidence for such Cu sparing is seen during fungal invasion of the kidney, when SOD1 expression declines and SOD3 increases (7,8).…”
mentioning
confidence: 99%
“…Specifically, C. albicans and closely related fungi express a rare form of Mn-SOD (SOD3) that resides in the cytosol, the same location as Cu/Zn-SOD1. C. albicans will switch from expressing Cu/Zn-SOD1 to cytosolic Mn-SOD3 when Cu is low, a condition that occurs in the kidney during fungal infection 153154 . This adaptation allows C. albicans to maintain cytosolic SOD activity even in times of Cu depletion 153154 .…”
Section: Fungal Pathogensmentioning
confidence: 99%
“…C. albicans will switch from expressing Cu/Zn-SOD1 to cytosolic Mn-SOD3 when Cu is low, a condition that occurs in the kidney during fungal infection 153154 . This adaptation allows C. albicans to maintain cytosolic SOD activity even in times of Cu depletion 153154 . The arthropod fungal pathogen B. bassiana also contains dual cytosolic Mn and Cu/Zn-containing SODs and, moreover, expresses a pair of mitochondrial matrix SODs that use either Mn or Fe as a cofactor.…”
Section: Fungal Pathogensmentioning
confidence: 99%